Upconversion Nanocarriers Encapsulated with Photoactivatable Ru Complexes for Near‐Infrared Light‐Regulated Enzyme Activity. Issue 46 (12th October 2017) - Chen, Zhijun; Thiramanas, Raweewan; Schwendy, Mischa; Xie, Chaoming; Parekh, Sapun H.; Mailänder, Volker; Wu, Si
Abstract: Enzyme activity is important for metabolism, cell functions, and treating diseases. However, remote control of enzyme activity in deep tissue remains a challenge. This study demonstrates near‐infrared (NIR) light‐regulated enzyme activity in living cells based on upconverting nanoparticles (UCNPs) and a photoactivatable Ru complex. The Ru complex is a caged enzyme inhibitor that can be activated by blue light. To prepare a nanocarrier for NIR photoinhibition of enzyme activity, a UCNP and the caged enzyme inhibitors are encapsulated in a hollow mesoporous silica nanoparticle. In such a nanocarrier, the UCNP can harvest NIR light and convert it into blue light, which can activate the caged enzyme inhibitors. This photoactivation process is feasible in deep tissue because of the tissue penetration ability of NIR light. The nanocarrier is compatible to LNCaP, PC3, and SAOS‐2 cells, which show high enzyme expression. NIR irradiation induces release of the inhibitors and inhibition of enzyme activity in living cells. NIR light provides high spatiotemporal resolution to regulate enzyme activity in deep tissue. Abstract : Photon upconversion enzyme inhibition is employed to regulate enzyme activity using NIR light. Upconverting nanoparticles and caged enzyme inhibitors are encapsulated in hollow mesoporous silica nanoparticles. Upconverting nanoparticles convert near‐infrared light to blue light, which activates caged enzyme inhibitors. The activated enzyme inhibitors are released and inhibit enzyme activity in living cells.